IMPACT OF DEFORESTATION ON FORESTRY AND FOREST VILLAGE COMMUNITY INSTITUTION (LMDH) - Dwi Ekasari Harmadji; Sri Hastutik; Sonny Leksono; Achmad Mamduh (International Journal Labs, 2022)
The causes of deforestation in Indonesia have been widely discussed in the literature related to this matter, but this article discusses the impact and mitigation of deforestation in the Gunung Kawi forest area. The purpose of this study is to answer the questions that are at the heart of the problem, namely: (1) How do we define “forest”, “deforestation” and “LMDH” and “Role of Forestry” in the Indonesian context? (2) What is the principle of the implementation of the cooperation between Forestry Malang Regency and LMDH Wonosari (actors who are grouped as the indigenous people of Gunung Kawi) to reduce deforestation and forest land degradation? The research method uses a descriptive qualitative approach. The results of this study provide suggestions for Forestry Malang Regency to apply the principles of the Partnership Program with a Public Private Partnership which can eliminate the tendency to find a single cause of the failure of the cooperation program with LMDH Wonosari. Deforestation can be tackled by planting coffee trees “intercropping” and Taro Beneng plants among the pine trees in the Gunung Kawi Forest. Suggestions for future researchers to be able to know with certainty the involvement of the Malang Regency Government and Forestry in providing deforestation and reforestation data in the Gunung Kawi Forest.